Integration of Early Infant Diagnosis of HIV Services Into Village Health Clinics in Ntcheu, Malawi: An Exploratory Qualitative Study - Chinguwo, Felix (J Int Assoc Provid AIDS Care, 2021)
Integration of Early Infant Diagnosis(EID) of HIV into Village Health Clinics (VHCs) would increase the uptake of services. This study assessed mothers and health care workers’ acceptability of integration of EID of HIV services into VHCs in Ntcheu, Malawi. We conducted an exploratory qualitative study in the phenomenological tradition among 20 mothers of either HIV exposed or non-exposed infants and 18 health care workers (HCWs) from February to July 2019. We analyzed the data using a thematic approach and guided by the theoretical framework for acceptability. There were positive perceptions of the integration of services. Acceptability is influenced by attitudes, perceived burden, intervention coherent services, and perceived effectiveness of services. The successful integration of EID of HIV into VHCs requires strengthening of the health system and community awareness. Efforts to mitigate stigma should be prioritized when integrating the services to optimize uptake of the services at a community level.